2014
DOI: 10.1080/19443994.2013.812993
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of natural coagulants from non-plant-based sources for water and wastewater treatment—a review

Abstract: A B S T R A C TThe natural polymers used in water and wastewater treatment systems include starches, galactomannans, cellulose derivatives, chitosan, microbial polysaccharides, gelatin, glues, and alginate. These natural coagulants are capable of treating water from high to low turbid water and having removal efficiency of sometimes more than 98% that can be used for drinking purposes. Naturally occurring coagulants are usually presumed safe for human health, while there is a fear that using aluminum salts may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…In the case of natural polymers like alginate, it may generally follow the mechanism (d). Calcium alginate gel combines with the dispersed particle irrespective of the charge and leads to flocculation [23]. At the end of these loops, it may attach with another particle and forms a bridge between the two particles, which is known as the bridging mechanism of floc-culation.…”
Section: Coagulation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of natural polymers like alginate, it may generally follow the mechanism (d). Calcium alginate gel combines with the dispersed particle irrespective of the charge and leads to flocculation [23]. At the end of these loops, it may attach with another particle and forms a bridge between the two particles, which is known as the bridging mechanism of floc-culation.…”
Section: Coagulation Mechanismmentioning
confidence: 99%
“…The coagulation process can be enhanced by any one of the mechanism: charge neutralization along with bridging the particles or by the gel formation of calcium and alginate. Calcium alginate gel combines with the dispersed particle irrespective of the charge and leads to flocculation [23]. Grant et al [24] reported that when natural long-chain polysaccharides 21 , it forms an egg box structure which leads to a stable gel formations.…”
Section: Coagulation Mechanismmentioning
confidence: 99%
“…These disadvantages have recently stimulated researches on the exploration of potential natural coagulant. Various nonplant [e.g., chitosan (Alaba et al 2018), alginate (Saranya et al 2014)] and plant-based coagulants, such as Ipomoea dasysperma (Sanghi et al 2006), Moringa stenopelata (Dalvand et al 2016), Acacia mearnsii de Wild (Beltran-Heredia et al 2011), and Plantago ovata (Ramavandi and Farjadfard 2014), have been proposed as natural coagulant to treat textile wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…However, the coagulation performance of metal coagulants may not satisfy the increasing demand for NOM removal, and thus numerous researchers have focused on the use of natural coagulants in drinking water treatment [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%